​Soil Health Assessment and Management Framework - Desta, Gizaw; Agegnehu, Getachew; Patil, Mukund; Choudhari, Pushpajeet L.; Legesse, Gizachew; Desalegn, Henok; Botoman, Lester (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Soils deliver valuable ecosystem services, such as the release of nutrients from soil organic matter, water storage and transfer (Tahat et al., 2020), water and air quality (Doran and Zeiss, 2000), food security (Lal and Stewart, 2010), cultural heritage, etc. Hence, it is vital to the environment and society that soil functions and its quality are maintained (Blum, 2005). Soil quality and soil health are often used interchangeably, but generally refer to the same concept (Bünemann et al., 2018), i.e., a soil's capacity to function as a dynamic living ecosystem to sustain plant and animal health and environmental quality. Although both terms address the physical, chemical, and biological aspects of soil, soil health is a broader, more holistic concept that encompasses the long-term sustainability and vitality of the soil as a living system, while soil quality sometimes focuses on more specific, land-use-dependent functions and attributes.